The Legal Position of Therapeutic Contracts in Plastic Surgery Procedures and Medical Dispute Resolution in Indonesia - Umu Istikharoh; Francis Maryane Pattynama; Ahmad Heru Romadhon; Rahayu Sri Utami (Smart Society, 2026)
The rapid expansion of aesthetic plastic surgery in Indonesia, driven by technological advancement and the increasing influence of digital media on beauty perception, has intensified legal challenges concerning patient protection, professional accountability, and the enforceability of therapeutic contracts. This development is reflected in the rising number of medical disputes and disciplinary complaints, as well as the growing demand for aesthetic medical services across the region. These conditions have generated doctrinal uncertainty regarding the legal classification of therapeutic contracts in elective medical procedures, where civil contractual principles intersect with medical ethics and professional standards. This study aims to clarify the legal nature of therapeutic contracts in plastic surgery and to examine medical dispute resolution mechanisms as a framework for balanced legal protection of physicians and patients. A normative legal research method is employed using statutory, conceptual, and doctrinal approaches. The study analyzes key legal instruments, including the Indonesian Civil Code, Law No. 17 of 2023 concerning Health, Government Regulation No. 28 of 2024, and Minister of Health Regulation No. 290/Menkes/Per/III/2008, supported by health law doctrines and principles of professional liability. The findings demonstrate that therapeutic contracts in plastic surgery constitute a hybrid legal construct situated at the intersection of civil contract law, health regulation, and medical ethics. This hybridity generates doctrinal tension between contractual autonomy and professional medical responsibility, particularly in determining liability when surgical outcomes diverge from patient expectations in elective aesthetic procedures. Medical dispute resolution operates through a structured dual mechanism: preventive protection, including informed consent, medical record governance, professional standards compliance, and ethical supervision; and repressive protection through alternative dispute resolution and litigation pathways, with a normative preference for non-litigation settlement. This study concludes that although Indonesian health law provides a regulatory foundation for therapeutic contracts and dispute resolution mechanisms, it still lacks a coherent doctrinal taxonomy to clearly differentiate contractual liability from professional medical responsibility in aesthetic surgery practice. By repositioning therapeutic contracts as a hybrid legal entity within health law discourse, this study contributes to theoretical refinement in medical law and offers practical implications for strengthening regulatory coherence, dispute prevention mechanisms, and legal certainty in aesthetic medical services.